Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1212/wnl.50.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic processing during repetitive transcranial magnetic stimulation

Abstract: To determine if linguistic processing could be selectively disrupted with repetitive transcranial magnetic stimulation (rTMS), rTMS was performed during a picture-word verification task. Seven right-handed subjects were trained in two conditions: picture-word verification, which required the subject to verify whether the picture of an object matched the subtitle name on the same page, and frame verification, which required subjects to verify whether there was a rectangular frame around the combined object pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 15 publications
1
58
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first magnetic stimulation study highlighting that the right parietal cortex is involved in word recognition (but see Flitman et al, 1998, where left but not right parietal stimulation affected picture-word matching). Previous studies that have used TMS in reading tasks have focussed more on regions of the brain that are typically believed to be involved in motor-or linguistic processes, or early visual processing.…”
Section: Discussionmentioning
confidence: 88%
“…To the best of our knowledge, this is the first magnetic stimulation study highlighting that the right parietal cortex is involved in word recognition (but see Flitman et al, 1998, where left but not right parietal stimulation affected picture-word matching). Previous studies that have used TMS in reading tasks have focussed more on regions of the brain that are typically believed to be involved in motor-or linguistic processes, or early visual processing.…”
Section: Discussionmentioning
confidence: 88%
“…Converging evidence comes from studies using TMS which have inhibited right hemispheric areas in recovered patients. Flitman et al (121), for instance, showed that magnetic stimulation may affect the compensatory functions of right-sided areas as it induces transient language disorders in these patients. However, contradicting this finding, other results have suggested that inhibition of right-sided premotor regions can improve naming abilities in nonfluent aphasic patients at a very late stage (260).…”
Section: Language Recovery Poststrokementioning
confidence: 99%
“…Applied to the visual cortex for example, strong TMS can produce phosphenes and stimuli of lower intensity induce transient scotomas (Hallett, 2000). Moreover, other functions, such as linguistic processing, can be investigated with rTMS (Flitman et al, 1998). A neuromodulatory effect of subthreshold high-frequency rTMS has been observed in 10 subjects.…”
Section: Basic Effectsmentioning
confidence: 99%